Infant, pediatric and adult well visit trends before and during the COVID-19 pandemic: a retrospective cohort study - Joanne Salas; Leslie Hinyard; Ann Cappellari; Katie Sniffen; Christine Jacobs; Natalie Karius; Richard A. Grucza; Jeffrey F. Scherrer (BMC, 2022)
Abstract Background Adult well visits declined during COVID-19, but literature is inconsistent in regard to whether childhood well visits declined. We determined if the COVID-19 pandemic was associated with a change in well visits among infants, children, adolescents and adults before, compared to during the COVID-19 pandemic, including through the emergence of the Delta variant. Methods De-identified electronic health care data came from a multi-state Midwest health care system. Eligible patients (n = 798,571) had ≥ 1 well visit between 7/1/2018 and 6/30/2021. Trends in well visits per month for children (< 1, 1-4, 5-11, 12-17 years) and adults (18-39, 40-64, ≥ 65 years) over 3-years were assessed using Joinpoint regression models and monthly percent change (MPC). Results Well visits remained stable for infants (< 1 year of age) (MPC = -0.1; 95% CI = -0.3, 0.1). For children 1-4 years and all adults, visits were stable prior to 2020, decreased from 1/2020 to 4/2020 (MPC range -20 to -40), increased from 4/2020-7/2020 (MPC range 30 to 72), and remained stable after 7/2020. Children 5-17 had seasonal variation in visits where low points occurred in Jan/Feb 2019 and high points in Aug 2019 (start of school year); however, the low point in 2020 occurred in April 2020 and the seasonal variation normalized after this. Conclusions In a large Mid-western health care system, infant well visits did not decline at the onset (3/1/2020) of the COVID-19 pandemic. Although well visits for all other ages decreased to a low point in 4/2020, a rapid return to pre-pandemic utilization rates occurred by 7/2020. The brief decrease in preventive care may have had little impact on health.